2019
DOI: 10.1038/s41389-019-0177-4
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA GAS5 acts as proliferation “brakes” in CD133+ cells responsible for tumor recurrence

Abstract: Presence of quiescent, therapy evasive population often described as cancer stem cells (CSC) or tumor initiating cells (TIC) is often attributed to extreme metastasis and tumor recurrence. This population is typically enriched in a tumor as a result of microenvironment or chemotherapy induced stress. The TIC population adapts to this stress by turning on cell cycle arrest programs that is a "fail-safe" mechanism to prevent expansion of malignant cells to prevent further injury. Upon removal of the "stress" con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
(63 reference statements)
1
13
0
Order By: Relevance
“…However, cancer cells rely on glycolysis as their preferred energy source using a phenomenon called the Warburg effect, named after the German biochemist, Otto Warburg, who discovered that cancer cells used a different metabolic pathway than normal cells [ 75 ]. Multiple peer-reviewed publications from our group corroborate these observations as well [ 6 , 7 , 12 ]. Interestingly, the metabolic phenotype of CSCs appears to vary across different tumor types and tumor microenvironments.…”
Section: Regulation Of Cancer Stem Cell Metabolism By Ecmsupporting
confidence: 70%
See 2 more Smart Citations
“…However, cancer cells rely on glycolysis as their preferred energy source using a phenomenon called the Warburg effect, named after the German biochemist, Otto Warburg, who discovered that cancer cells used a different metabolic pathway than normal cells [ 75 ]. Multiple peer-reviewed publications from our group corroborate these observations as well [ 6 , 7 , 12 ]. Interestingly, the metabolic phenotype of CSCs appears to vary across different tumor types and tumor microenvironments.…”
Section: Regulation Of Cancer Stem Cell Metabolism By Ecmsupporting
confidence: 70%
“…This is manifested in the CSCs by enhanced resistance to therapy along with high metastatic potential. A recently published study from our group shows that under nutritional deprivation or hypoxia or due to chemotherapy treatment, the CD133 + CSC population markedly upregulates the long-noncoding RNA GAS5 [ 12 ]. This promotes quiescence in this population of CSCs, thereby helping these cells to survive during these stressful conditions.…”
Section: Extracellular Matrix As a Niche For Cancer Stem Cell Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in cancer have suggested that GAS5 puts a "brake" on cell proliferation, thereby acting as a potential tumor suppressor in various cancers (46). Also, overexpression of GAS5 has been shown to increase apoptosis and reduce cell cycle progression in T cell lines and PBMCs (47).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of DANCR transcript reduced self-renewal capacity and quiescence of LSCs in a AML murine model[ 137 ]. The lncRNA growth arrest-specific 5 was highly expressed in the CD133 + pancreatic CSC population and was found to suppress proliferation by inhibiting glucocorticoid receptor-mediated cell cycle regulation[ 138 ].…”
Section: Quiescence Of Cscs and Their Clinical Relevancementioning
confidence: 99%